1983
DOI: 10.1161/01.res.53.5.630
|View full text |Cite
|
Sign up to set email alerts
|

Factors modifying the early nondiuretic vascular effects of furosemide in man. The possible role of renal prostaglandins.

Abstract: Animal experiments have suggested that salt-balance, prostaglandin synthesis, and renal function are important determinants of the nondiuretic vascular effects of furosemide. To investigate the influence of these factors in humans, we studied 10 normal volunteers and five anephric patients. The volunteers were studied on three occasions: when on a 10 mEq/day sodium diet, on a 250 mEq/day sodium diet, and on a 10 mEq/day sodium diet with indomethacin, 200 mg/day. The anephric patients were studied immediately a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
39
1
2

Year Published

1985
1985
2008
2008

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(44 citation statements)
references
References 25 publications
2
39
1
2
Order By: Relevance
“…In addition to venodilation, several investigators have reported increases in blood pressure and vascular resistance (34, 52) after loop diuretic treatment. The reduction in contractility of isolated Nkcc1 Ϫ/Ϫ portal veins is consistent with the hypothesis that the increased venous compliance in response to loop diuretics is due to inhibition of NKCC1 in the vasculature; however, the results of several studies (5,16,23) suggest that these effects might also be due to the release of vasoactive compounds from the kidney. If the kidney is involved, then inhibition of NKCC1, which is expressed in the extraglomerular mesangium and the glomerular afferent arteriole (25), could contribute to this effect.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…In addition to venodilation, several investigators have reported increases in blood pressure and vascular resistance (34, 52) after loop diuretic treatment. The reduction in contractility of isolated Nkcc1 Ϫ/Ϫ portal veins is consistent with the hypothesis that the increased venous compliance in response to loop diuretics is due to inhibition of NKCC1 in the vasculature; however, the results of several studies (5,16,23) suggest that these effects might also be due to the release of vasoactive compounds from the kidney. If the kidney is involved, then inhibition of NKCC1, which is expressed in the extraglomerular mesangium and the glomerular afferent arteriole (25), could contribute to this effect.…”
Section: Discussionsupporting
confidence: 82%
“…Additional studies will be needed to determine the extent of the deficit in vascular contractility, the ionic basis for this defect, and whether it is the major mechanism of the observed hypotension. Given the expression of NKCC1 in renin-secreting cells of the glomerular afferent arteriole, it seems possible that alterations in the secretion of vasoactive compounds from the kidney might, as suggested by others (5,16,23), account for some of observed vascular effects of loop diuretics in vivo. The reduction in excitatory amino acid release observed in Nkcc1 Ϫ/Ϫ astrocytes (49) suggests that neuronal mechanisms could also be involved.…”
Section: Discussionmentioning
confidence: 94%
“…A high salt diet, pre-treatment with indomethacin and severely impaired renal function will prevent the acute venodilator effects of frusemide (Johnston et al, 1983a). In these situations acute frusemideinduced renin release and prostaglandin formation (PGE2, PGI2) are reduced.…”
Section: Discussionmentioning
confidence: 99%
“…Vascular responses to blocking NKCC1 with loop diuretics include direct vasodilatation, indirect vasodilatation through mediation of vasorelaxing prostaglandins, and reductions in the contractile responses to vasoconstrictors such as norepinephrine and ANG II (11,15). A reduction of arterial blood pressure has been reported in NKCC1 Ϫ/Ϫ mice using the tail cuff method (19,26).…”
mentioning
confidence: 99%